DIGITAL DISRUPTION IN FINANCIAL REPORTING: A CATALYST FOR REGULATORY COMPLIANCE IN INDONESIAN MSMES - Nurul Aisyah Rachmawati; Rizka Ramayanti; Rudi Setiawan (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2025)
The purpose of this study is to examine whether the acceptance of a financial report application affects micro, small, and medium enterprises (MSMEs) compliance in Indonesia. This study uses primary data obtained from a survey conducted in June-July 2022. The data obtained were afterward analyzed using path analysis with structural equation modeling. This research finds that the perceived ease of use and perceived usefulness of MSME actors have a positive and significant effect on the actual usage of the financial report application. Furthermore, the actual usage of the financial report application has also proven to have a positive effect on the compliance of MSME actors. The contribution of this research is to provide evidence that acceptance of financial reporting applications is a solution that can be used to overcome MSME constraints in compiling financial reports. The use of this application is also able to increase MSME compliance.